First‐Line Levofloxacin‐Based Triple Therapy Versus Standard Bismuth‐Based Quadruple Therapy for Helicobacter pylori Eradication in Saudi Arabia: A Retrospective Single‐Center Study - Abdulrhman Khaled Al Abdulqader; Turki Abdullah Alamri; Mahdi Abdullah Alhamad; Somaia Shehab El‐Deen; Abdallah Essa; Raed Abdullah Alfayez; Baqer Mohammed Albaqshi; Adnan Salah Almajed; Mohammed Yousef Alhassan; Ali Essa; Ahmed Abdullah Albadrani; Omar Alomair; et al. (Health Science Reports)
ABSTRACT Background and Aims Antibiotic resistance in Saudi Arabia has led to decreased efficacy of conventional triple therapy for Helicobacter pylori (H. pylori) eradication, prompting the development of alternative treatments like levofloxacin‐based triple and bismuth‐based quadruple therapies. However, comparative data regarding its efficacy are lacking. Therefore, this study's goal was to compare the efficacy of levofloxacin‐based triple therapy with that of standard bismuth‐based quadruple therapy as first‐line regimens. Methods This retrospective analysis included 197 treatment‐naïve adults with H. pylori infection who received levofloxacin‐based triple (levofloxacin + amoxicillin + PPI) therapy (n = 81) or standard bismuth‐based quadruple (bismuth + tetracycline + metronidazole + PPI) therapy (n = 116). H. pylori eradication was evaluated 4–8 weeks after medication administration using the 13C‐urea breath test, and variables that could affect the rate of success were examined. Results There were no differences between groups in terms of age, sex, nationality, or type of proton pump inhibitor (PPI) used. The bismuth‐based quadruple therapy group exhibited a markedly superior success rate compared to the levofloxacin‐based triple therapy group when the latter was administered for 7 or 10 days (81.03% vs. 6.66%, p < 0.001, and 81.03% vs. 36.1%, p < 0.001, respectively). However, when the levofloxacin‐based triple therapy was extended to 14 days, its H. pylori eradication rate became comparable to that of the 10‐day bismuth‐based quadruple therapy (81.03% vs. 80%, p = 0.898). Eradication rates for both regimens were similar for patients aged ≥ 60, non‐Saudi, when using omeprazole and those treated with levofloxacin‐based triple therapy for 14 days. Conclusion Quadruple treatment based on bismuth is superior to triple therapy based on levofloxacin for eradicating H. pylori in Saudi Arabia and should be used as a first‐line treatment. However, the 14‐day levofloxacin‐based triple treatment had an H. pylori eradication rate comparable to that of the 10‐day bismuth‐based quadruple therapy.